2001
DOI: 10.1046/j.1365-2141.2001.03194.x
|View full text |Cite
|
Sign up to set email alerts
|

Absence of platelet response after eradication of Helicobacter pylori infection in patients with chronic idiopathic thrombocytopenic purpura

Abstract: Eradication of Helicobacter pylori infection has been associated with the correction of thrombocytopenia in patients with idiopathic thrombocytopenic purpura (ITP). We have analysed the response to eradication of H. pylori in a series of 56 adult patients with chronic ITP. Forty patients had H. pylori infection (71%) that was eradicated in 23 of 32 evaluable patients (72%). Platelet counts did not significantly vary according to H. pylori treatment outcome. Three of 56 patients (5%) achieved a partial response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
83
2
5

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(98 citation statements)
references
References 5 publications
8
83
2
5
Order By: Relevance
“…[3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][28][29][30][31][32][33][34][35] The prevalence (51%) of bacterium …”
Section: Discussionunclassified
“…[3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][28][29][30][31][32][33][34][35] The prevalence (51%) of bacterium …”
Section: Discussionunclassified
“…The heterogeneity of the populations reported, the variable study designs, differences in inclusion criteria, differences in definition of platelet response, and concurrent ITP therapy, are some of the variables which may have influenced or confounded the results. For example, the highest response rate, reported by Gasbarrini et al [75] (100% response of platelet counts after eradication of H. pylori), may have been affected by concurrent steroid treatment, while in one of the studies which reported no response, a wash-out period of no therapy was required prior to eradication [88]. In summary, the current data suggests that H. pylori eradication can be considered for H. pylori-positive ITP patients [82], and the British Society of Hematology has listed H. pylori testing and eradication as a level III treatment for ITP [14].…”
Section: Predisposing Conditions and Molecular Mimicrymentioning
confidence: 96%
“…It was evident that some studies allowed concurrent ITP therapy but did not stipulate whether changes to this therapy were made in the post-eradication phase [13,20]. Some authors required a 1-3 month washout period of no therapy prior to eradication [57], while others allowed concurrent ITP therapy that had been stable for 1-6 months prior to eradication [19,56]. In some cases, the authors did not allow changes to concurrent ITP therapy after the eradication therapy had begun [22,29].…”
Section: The Unexpectedmentioning
confidence: 99%
“…Although a response was observed in 10 cohort studies [13][14][15]20,22,[27][28][29]54,55], the two cohorts that showed no or little improvement in platelet counts with eradication therapy included American or Spanish patients [24,57]. Prevalence rates for H. pylori in American patients (22%) compared to non-American patients (average 68%) in Table I may reflect different pathologic mechanisms for ITP in relation to H. pylori for these geographically different cohorts.…”
Section: The Unexpectedmentioning
confidence: 99%